Plumbum Exposure and MCV Value in Silver Human Workers in Semarang - Budi Santosa; Risma Intan Hidayah; Andri Sukeksi (Health Notions, 2022)
Plumbum enters through various environmental factors such as inhaled air, digestion, urine as much as 75-80%, feces 15%, and others such as sweat, hair, and nails. The impact of exposure to lead can affect erythrocyte index. The erythrocyte index is a limitation of the size and content of erythrocyte hemoglobin, the erythrocyte index examination consists of MCV MCH and MCHC. The purpose of this study was to determine the relationship between exposure to lead in the blood and MCV values in silver human workers. This type of research was analytic. 15 silver workers were taken from Jl. Soekarno Hatta Semarang. 8 ml samples were taken for examination of lead levels and MCV levels, put in a purple tube, then 5 ml of blood was examined for lead levels in the IDD laboratory using the ASS method, while 3 ml of blood was examined MCV levels in the Hematology Laboratory, Universitas Muhammadiyah Semarang using a hematology analyzer. The results showed that the lead levels in the high category was 15 samples at most with a percentage value of 100%, while the MCV had the highest number, namely in the normal category as many as 13 samples with a percentage value of 86.6. Statistical test using Pearson correlation showed p-value of 0.102. It can be concluded that there is no relationship between exposure to lead in the blood and the value of MCV. Keywords: silver human workers; MCV; plumbum exposure